A three-level neutral-point clamped dual-output converter - Ahmed S. Hussein (2022)
This paper introduces a novel three-level dual-output neutral-point clamped converter. The proposed topology has both the advantages of a reduced power component count and complete independent control of its outputs. The converter is operated using Finite-Control-Set Model Predictive Control (FCS-MPC). The mathematical model of the proposed converter is developed and is used in the FCS-MPC algorithm to realize the desired output currents and balance the neutral point voltage. The operation of the proposed topology is verified by comparing simulation and experimental results. Moreover, a comparison with the flying capacitor based dual-output converter, in terms of the total harmonic distortion and the average device switching frequency, is presented.